The Influence of Financial Literacy on PayLater usage with Self-Control as Moderating Variable Among Gen-Z in Jombang Regency - Fernanda Sari; Omi Pramiana (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
This study aims to analyze the influence of financial literacy on the use of Buy Now Pay Later (PayLater) with self-control as a moderating variable among Generation Z in Jombang Regency. The utilization of digital technology provides convenience but also brings risks such as digital dependency and mental health issues. Fintech, especially PayLater, is increasingly popular among Gen Z due to its easy access and flexibility, but its use may lead to financial risks if not supported by adequate financial literacy and self-control. This research uses a quantitative approach with field study research, involving 100 Gen Z respondents who have used PayLater in Jombang Regency. Data were collected through an online questionnaire tested for validity and reliability, and analyzed using simple regression analysis and moderation tests with SPSS. The results indicate that financial literacy does not directly affect PayLater usage. However, self-control is a significant moderating variable, strengthening the relationship between financial literacy and PayLater usage. Respondents with high self-control use PayLater more wisely, even if their level of financial literacy is not high